2013
DOI: 10.1063/1.4799731
|View full text |Cite
|
Sign up to set email alerts
|

Design and mechanism of cost-effective and highly efficient ultrathin (< 0.5 μm) GaAs solar cells employing nano/micro-hemisphere surface texturing

Abstract: Low aspect-ratio nano/micro-hemisphere surface texturing is introduced for improving light management in ultrathin GaAs solar cells. A 200 nm thick film textured by the optimal GaAs nano/micro-hemisphere array with both the hemisphere diameter and array periodicity of 500 nm can achieve >90% light absorption from 1.44 to 2.5 eV, lying in the high photon density energy regime of the solar spectrum for GaAs. The excellent light confinement and low aspect ratio, which is thus convenient for conformal deposition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Li et al showed that high absorption of light (>90%) is possible by employing low aspect ratio 3D hemispherical micro features on GaAs solar cells. 16 Numerical investigations showed that local heat transfer increases greatly by employing 3D hemispherical micro features on the surface. 17…”
Section: Introductionmentioning
confidence: 99%
“…Li et al showed that high absorption of light (>90%) is possible by employing low aspect ratio 3D hemispherical micro features on GaAs solar cells. 16 Numerical investigations showed that local heat transfer increases greatly by employing 3D hemispherical micro features on the surface. 17…”
Section: Introductionmentioning
confidence: 99%